Ecos do feminismo no ENEM 2015 : uma análise dialógica de discursos - Oliveira, Giselle Marques Ramos de (2017)
From this research, we seek to carry out a dialogical analysis of discourses disseminated in the online media field about the controversy surrounding the contents of the National Examination of Secondary Education (Enem) in October 2015. For the study, we selected Speeches from different authorities in the political sphere, education on the subject in news portals and on social networks. Through this study, we try to highlight the ideological positions present in the statements and to perceive the way in which the discourses dialogue, verifying the recurrences, the political assessments regarding the gender discussions by the enunciators. As a method, we are based on Dialogical Discourse Analysis (DDA), coined by Brait (2005) and anchored in the studies of Bakhtin and his Circle. Besides the theoretical reference of study on the feminisms, such as Joan Scott, Margareth Rago and Joana Maria Pedro and Ana Maria Marques, as well as, we dialogue with the philosophy of Márcia Tiburi. The results of our analysis indicate that the speakers use the specific intonation, by accentuating and reemphasizing the words, giving them a bivocal sense, which allows for the distancing of the discourses mentioned, and sometimes the approximation. In addition, we verify the use of the authoritarian word as a single discursive truth, as well as the creation of open controversy and veiled controversy, according to the writers intention. Finally, we highlight the recurrences of the linguistic strategies observed in articulists statements: the use of the word of others; The choice of nouns and adjectives united, in the attempt to characterize positively, or negatively the discourse of others; The repetition of words with the intention of imposing a single ideological position; The use of quoted speech, direct and indirect; Besides the predilection for certain written records, as use of the the quotation marks, the capital letters and the use of the comma. These results demonstrate the importance of research in Dialogical Discourse Analysis for contemporary discursive practices, in our case the dialogic relations between gender studies and education.